VIOLENCE AGAINST ELDERLY WOMEN - Oliveira, Ademara Aparecida de; Lazarini, Carlos Alberto; Marin, Maria José Sanches; Alarcon, Miriam Fernanda Sanches; Moraes, Magali Aparecida Alves de; Higa, Elza de Fátima Ribeiro (Cogitare Enfermagem, 2023)
Objective: To analyze the understanding of older women about violence in this age group. Method: Qualitative research carried out between November 2021 and January 2022 with 40 women over 60 years old, attended in the Primary Health Care Network, in a medium-sized municipality in the interior of the state of São Paulo - Brazil. The data obtained were analyzed in the light of Hermeneutics-Dialectics. Results: Five analytical categories were identified: 1. Understanding of violence against the elderly woman; 2. Factors that trigger violence against the elderly woman; 3. Suggestions for actions to prevent violence against the elderly woman; 4. Resources that older women who are victims of violence can access; 5. Nonconformity with violence against the elderly woman. Final Considerations: In the light of Hermeneutics-Dialectics, a series of perceived violence against the elderly woman in society was evidenced, with emphasis on physical, disrespect and financial abuse.